2015
DOI: 10.1177/1087054715616186
|View full text |Cite
|
Sign up to set email alerts
|

Positive Bias in Teenage Drivers With ADHD Within a Simulated Driving Task

Abstract: Results inform prevention and intervention efforts for teenage drivers with ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…Several previous studies found that those with ADHD reported driving more miles 8,41 ; however, these studies were limited in the authors' assessment of exposure (eg, usual driving at time of survey) and reliance on self-reports, which might have been subject to positive illusory bias. 15 In our analyses, we accounted for time since licensure, a proxy for exposure and itself critically important given that crash risk declines over the initial years of driving. In this study, we also used crash and violation events as proxies for engagement in risky driving behavior; future studies in which naturalistic driving methodologies are used would provide additional crucial insights.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies found that those with ADHD reported driving more miles 8,41 ; however, these studies were limited in the authors' assessment of exposure (eg, usual driving at time of survey) and reliance on self-reports, which might have been subject to positive illusory bias. 15 In our analyses, we accounted for time since licensure, a proxy for exposure and itself critically important given that crash risk declines over the initial years of driving. In this study, we also used crash and violation events as proxies for engagement in risky driving behavior; future studies in which naturalistic driving methodologies are used would provide additional crucial insights.…”
Section: Discussionmentioning
confidence: 99%
“…7,[9][10][11] However, these studies revealed inconsistent findings and involved samples that were either small or more severely affected. 9,10 Moreover, drivers with ADHD have been found to overestimate their driving competence, 15 challenging the validity of self-reported measures and highlighting a critical need for studies in which objective traffic safety data are used.…”
mentioning
confidence: 99%
“…There is also evidence that parental ratings may be more valid than self-reports of behaviors that are socially undesirable. Adolescents and young adults with ADHD were less likely to self-report the presence of mild and moderately severe problematic behaviors compared to parent-report (Sibley et al, 2010) or objective observations (e.g., Fabiano, Schatz, et al, 2018).…”
Section: Bias In Ratings Of Individuals With Adhdmentioning
confidence: 87%
“…In adolescents with ADHD, a PIB in social competence has been shown to be stable over time (Bourchtein, et al, 2017). Research on PIB in adults and young adults with ADHD has often focused on ability and performance assessments, showing an overestimation of performance relative to non-ADHD comparison groups and objective assessments (e.g., Fabiano, Schatz, et al, 2018; Knouse, Bagwell, Barkley, & Murphy, 2005; Prevatt, Proctor, Baker, Garrett, & Yelland, 2012). Furthermore, a positive bias in self-perceptions over time was shown to be inversely related to depression in adolescents, which is speculated to be a function of the higher need for self-protection in the social domain during this developmental period (Hoza et al, 2010).…”
Section: Bias In Ratings Of Individuals With Adhdmentioning
confidence: 99%
“…Learning occurs when we’re paying attention, so we expect individuals with ADHD to learn a little less than others from every lesson. Plan to practice more than you think you will need to: Teens with ADHD tend to overestimate their driving abilities (Fabiano et al, 2018), and their parents may be less likely to implement optimal strategies for helping teens learn to drive. Evidence from videotapes of parents teaching their teen with ADHD to drive show an over-reliance on critical comments and an under-usage of positive comments for appropriate driving (Schatz et al, 2014).…”
Section: Break It Downmentioning
confidence: 99%